Pengaruh Variasi Temperatur Quenching terhadap Kekerasan, Kekuatan Tarik, dan Keuletan Baja AISI 1045: Studi Eksperimental terhadap Perubahan Sifat Mekanik dan Mikrostruktur pada Baja Karbon Sedang - syahputra, arya; Bagaskara, Aidil akbar (Jurnal Ilmiah Teknik Mesin, Elektro dan Komputer, 2025)
Abstract: This research systematically concentrates on the effect of different dyeing temperatures on the mechanical properties of AISI 1045 steel which has an important role in the field of mechanical engineering. These findings are important for the development of engineering components such as shafts and gears. This study aims to analyze the effect of quenching temperature variations on the hardness, tensile strength, and ductility of AISI 1045 steel experimentally. Heat treatment was carried out through samples up to an austenization temperature of 850°C with a holding duration of 30 minutes, followed by flash dipping (rapid cooling) using water media at temperature variations of 5°C, 15°C, 25°C, and 35°C. Each treatment was carried out five times and statistical analysis was given to obtain representative data. Observation of microstructures using serial light microscopy was carried out including evaluation. The results showed a close relationship between the decrease in coolant temperature and the increase in hardness and tensile strength. However, there is an opposite correlation with material durability. The highest hardness, 58 HRC, and the strongest tensile strength, 1250 MPa, were obtained for samples cooled at 5°C. Microstructure observations show a more dominant martensite formation at cooler immersion temperatures. The results of this study provide insight into the correlation with the transformation of the mechanical and microarchitectural characteristics of AISI 1045 steel.